Factors Affecting the Preference for Living Arrangement of the Overseas Filipino Workers in Bahrain - Dr. Maria Cecilia P. Lagaras; Dr. Maria Cecilia P. Lagaras (International Journal of Engineering and Management Research, 2019)
This study aimed to determine the factors affecting the preference for living arrangement of the Overseas Filipino Workers in Bahrain as they age. Data were from 35 respondents using descriptive, self-administered questionnaire. They were chosen using a non-probabilistic sampling. The study found out that respondents agree to live independently and they prefer to live independently rather than to live with the children. Further, they agree that they need in-home care when incapable of independent living but disagree on both variables; “don’t want to leave the assets behind” and “willing to give up my properties to the children”. Moreover, data suggests that income is highly significant in making decision on to live independently. It can be viewed that respondents have average monthly income of Php123,571.00 (2,360.39) and majority of them have pension plan. The respondents’ average age and civil status have significant relationship to live independently. Most of them are still young couples with an average age of 40. The study then concludes that income, age and civil status are the compelling factors to decide to live independently. Pre-retirees strive to for a more financially secure retirement by planning and preparing for it. The findings conform to the U-shaped pattern of life movement wherein parents are living with the children, then become independent, and in later, in their late life, co-reside back with the children or relatives for in-home care.